A formação do professor para a educação infantil: apontamentos para a formação do leitor. - Reis, Jessé Camatari (2017)
This paper aims to indicate elements for the training of teachers who work in children's education, as well as their interventions in the constitution of the reader subject, based on the perceptions of the pedagogical teacher of the Pedagogia / Parfor course (Decree 6755/09). It is assumed that the interventions of the teacher in the classroom can contribute to the constitution and formation of the reader. The research, of qualitative approach, is developed in three stages. The first focuses on the contribution of scholars on the subject of reading, evidencing the work of Monteiro Lobato and official documents, which deal with reading practices for children's education. The second one is developed through the application of a questionnaire to the teacher-students of Pedagogy / Parfor. And the third occurs through interviews with teacher trainers. When dealing with teacher training for the formation of the reader, three categories of analysis are identified: reading habits; Influence of reading in the formation of the reader; And challenges / difficulties in the context of teacher training for the teaching performance in the formation of the reader. The results show the importance of discussing and problematizing reading and reading, as well as the role of teachers and their interventions in the formation of new readers in the area of early childhood education.